Apoptosis-inducing factor starts its activity within mitochondria revealed by in situ vibrational probes - Jinyu Zhu; Yi Liao; Mengfan Feng; Li Song; Wei Li; Linjun Cai; Xiao Xia Han (Proceedings of the National Academy of Sciences, 2026)
Apoptosis-inducing factor (AIF) is a flavoprotein located in the mitochondrial intermembrane space, and it is believed to trigger caspase-independent cell death after its release from the mitochondria into the nucleus. Here, the proapoptotic activity of AIF within mitochondria and the underlying molecular mechanism are explored using label-free vibrational spectroscopy and imaging. Electron transfer between AIF and cytochrome c (Cyt c ) is evidenced by resonance Raman spectroscopy, and the details of their interaction are revealed through molecular dynamics simulations. We elucidate the nicotinamide adenine dinucleotide (NADH)-AIF-dependent generation of reactive oxygen species (ROS) and its correlation with phospholipid peroxidation at the molecular level. With in situ Raman probes, our results verified the synergistic contribution of AIF and Cyt c to mitochondrial membrane permeabilization via a ROS-independent pathway. Remarkably, NADH-dependent Cyt c release from isolated mitochondria is clearly monitored by in situ and real-time Raman spectroscopy, and our findings prove the proapoptotic role of NADH, further supported by flow cytometry. This function of AIF has implications for a deeper understanding of cell death executors and would open up therapeutic strategies for cancer.